Pengetahuan, sikap, dan faktor risiko lingkungan pada rumah tangga dengan riwayat leptospirosis di kota Yogyakarta dan kabupaten Bantul - Defryana Rakebsa; Citra Indriani; Widagdo Sri Nugroho (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Epidemiology of leptospirosis in Yogyakarta and BantulPurposeThe purpose of this study was to determine the relationship knowledge, attitude, and environmental factors with the incidence of leptospirosis.MethodsA case-control study was conducted in November 2016 in Yogyakarta city and Bantul district on 242 respondents. The case was leptospirosis patients that recorded in the Yogyakarta and Bantul District health offices within the period of June 2014 to June 2016. Controls were households in the same neighborhood as the case and had no history of leptospirosis, with case and control comparisons 1:1. Rat-catching was done inside the house and in the rice fields. ResultsKnowledge (OR: 1, 95% CI: 0.58-1.71, p-value: 1) and attitude (OR: 0.8, 95% CI: 0.47-1.40, p-value: 0 .44) had no significant association with leptospirosis incidence. The presence of rats in the home has no significant relationship with leptospirosis incidence (OR: 0.7, 95% CI: 0.15-3.78, p-value: 0.73). The multivariate analysis found that the distance of house to open sewer (OR: 2.96, 95% CI: 1.22-7.14) and the presence of in-house waste (OR: 2.03, 95% CI: 1.14-3.62) had a significant association with leptospirosis incidence.ConclusionThere was no statistically significant relationship between knowledge and attitude with leptospirosis incidence. Environmental factors such as the distance of house to open sewer and the presence of in-house waste have a statistically significant relationship with the incidence of leptospirosis. Two of the 4 serum mice examined with a positive MAT method contained Leptospira sp. with Benjamin serovar Benjamini strain.